Charles-Édouard Jeanneret’s Local Patriotism in La Construction des villes and Erneuerungsbewegung in Germany - Sayuri Hayakawa; Takahiro Taji (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
In 1910, Jeanneret began writing a text entitled La Construction des villes, when regionalism was en vogue on a central European scale. The text, however, was never published. We will first examine the content and ideological background of the local patriotism depicted in the text. Then, we will analyze the relationship between Jeanneret’s work and that of Paul Schultze-Naumburg, which is considered to be the source of his patriotism.